Latest on the pathology of drug-eluting stents. (December 2009) - Ladich, Elena; Vorpahl, Marc; Nakano, Masataka; Virmani, Renu
The introduction of drug-eluting stents (DES) has significantly reduced restenosis when compared with bare-metal stents and are considered the standard of care in the treatment of symptomatic coronary artery disease. However, late stent thrombosis (LST), potentially resulting in a fatal occlusion of the vessel, emerged as a major concern in first-generation DES (polymer-based sirolimus- and paclitaxel-eluting stents). Pathologic studies of patients dying from late DES thrombosis showed that the underlying mechanism is delayed healing, characterized by poor endothelialization of stent struts and persistence of fibrin. Additional risk factors for LST include long lesions, left main coronary artery disease, bifurcation stenting, underlying ruptured plaques and hypersensitivity reactions. Most recently, correlation of intravascular ultrasound findings with histopathological analysis of thrombus aspirates in patients with very late DES thrombosis showed eosinophilic infiltrates were associated with intravascular ultrasound evidence of vessel remodeling leading to secondary stent malapposition. New DES technologies include biodegradable polymers and stents, polymer-free drug delivery and prohealing approaches. Further preclinical testing and evaluation through large clinical trials is needed to determine the safety and efficacy of future DES in clinical practice.